Elaboración de un manual de buenas prácticas de manufactura en la empresa de chocolates Alamor - Andrade Villavicencio, Wellington Geovanny (2024)
The objective of this research was to create a Good Manufacturing Practices (GMP) manual for the Alamor chocolate company to meet the standards outlined in ARCSA Resolution 067-2015 by standardizing Standard Operating Procedures (SOPs). The methodology employed consisted of three stages. The first stage involved conducting a survey with the company's legal representative, Engineer Rocío Mora, to gather information on the company's standardized processes and sanitization protocols. In the second stage, compliance with the SOPs was evaluated using a checklist regulated by ARCSA. Finally, a training plan was developed for the staff, focusing on the necessity of effectively adopting and implementing GMPs to ensure product safety during chocolate production. The results indicate an 82.66% compliance rate, reflecting a strong commitment to quality standards. However, 6% of the criteria are unmet, and 11.33% are not applicable, highlighting areas for improvement and adaptation, such as establishing a testing laboratory. In conclusion, Alamor demonstrates a solid commitment to GMP compliance and quality standards.